Ion‐Induced Defects in Graphite: A Combined Kelvin Probe and Raman Microscopy Investigation. Issue 19 (29th May 2019) - Rodriguez, Raul D.; Khan, Zoheb; Ma, Bing; Mukherjee, Ashutosh; Meszmer, Peter; Kalbacova, Jana; Garratt, Elias; Shah, Harsha; Heilmann, Jens; Hight Walker, Angela R.; Wunderle, Bernhard; Sheremet, Evgeniya; et al.
Abstract : Carbon nanomaterials are important for future sensors and electronics. Defects determine the material properties, therefore, it is critical to find new ways to investigate defects at the nanoscale. In this context, Raman spectroscopy (RS) is the tool of choice to study defects in carbon nanomaterials. On the other hand, Kelvin probe force microscopy (KPFM) provides structural and surface potential information at the nanoscale. Here, the authors demonstrate the synergistic application of these methods in the investigation of ion‐beam‐induced defects in graphite. KPFM and RS imaging are used for visualizing ion‐induced defects in a wide range of ion doses from 10 10 to 10 16 ions cm −2 . For the lower range of ion dose, the authors find that RS provides image contrast for the different defect regions in graphite up to a dose of 5 × 10 13 ions cm −2 . For higher doses, the sp 2 carbon concentration becomes so small that the Raman spectra get dominated by broad amorphous carbon bands. For this dose range, the KPFM contrast allows the defective regions to be differentiated. This contrast in KPFM originates from sp 3 carbons that act as charge traps. The results show that KPFM and Raman microscopy make a powerful and necessary combination for studying the spatial distribution of defects in carbon. Abstract : Focused ion beam technology and techniques leveraged to control defect generation in graphite. The combination of Kelvin probe force microscopy and Raman spectroscopy imaging makes visualizing these defects in a broad range of ion dose possible, from the pristine graphite up to complete carbon amorphization.